THE EFFECTS OF COVID-19 PANDEMIC ON ENVIRONMENTAL CONDITIONS IN THE SPECIAL CAPITAL REGION OF JAKARTA, INDONESIA - Priyaji Agung Pambudi; David Febraldo Panjaitan (Universitas Lambung Mangkurat, 2023)
The Covid-19 pandemic that is getting worse, the Government responded by issuing PSBB and WFH policies with positive and negative effects in DKI Jakarta as national economic growth. The study aimed to analysis environmental effects. This qualitative research used literature review sourced from articles, government reports, institutional reports, and validated popular media. The policies have some significant effects on people's lives and environmental stability. The positive effects included the decline in PM2,5 with the highest value of 31,31% in West Jakarta, 27.80% in East Jakarta, and 25.74% in Central Jakarta. There was an improvement in air quality; the decline in electricity consumption was 7.24% in the industrial sector, 8.70% in business centers, 2.43% in government buildings, and 620 tons/day reduced waste. The adverse effects included: the closure of 3,570 companies and 1,225,725 workers doing WFH; increased household electricity consumption by 4.76%; decreased Commuter Line passengers by 82.10%; a decrease in Transjakarta passengers by 87.60%; and increased household waste by 36%. The pandemic harmed the socio-economic and had a positive effect on the environment. Pandemics provide an opportunity for humans to reflect on their behaviour and how they should interact with nature in post-pandemic encourage pro-environmental behaviour to support sustainable development.